1992
DOI: 10.1017/s0021859600012181
|View full text |Cite
|
Sign up to set email alerts
|

Viability of axillary buds of white clover (Trifolium repens) in grazed pasture

Abstract: SUMMARYStolon nodes of white clover were sampled monthly for 18 months from continuously grazed (set stocked) and rotationally grazed pastures in New Zealand. Both pastures were stocked at 22·5 ewes plus lambs/ha. Axillary buds were classified into viability categories using an incubation technique. On average, 54% of nodes had non-viable or dormant buds, 25% had axillary buds that were viable but non-active and 0·1% bore reproductive buds. Although 21% of buds emerged, only 8·5% of nodes bore live branches. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that clonal plants may respond to unfavourable growth conditions (e.g. intense shading) by increasing investment to flowering at the expense of vegetative growth (Watson 1984;Geber, Watson & Furnish 1992;Newton et al 1992). Such a reaction has been interpreted as an escape mechanism that enables offspring to reach more favourable growth conditions through dispersal in space and time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that clonal plants may respond to unfavourable growth conditions (e.g. intense shading) by increasing investment to flowering at the expense of vegetative growth (Watson 1984;Geber, Watson & Furnish 1992;Newton et al 1992). Such a reaction has been interpreted as an escape mechanism that enables offspring to reach more favourable growth conditions through dispersal in space and time.…”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of nodes bearing branches after culture in the glasshouse on stolons from both rejected and grazed areas (80-90 %) suggests that most of the axillary buds which had not developed into branches in the field were viable. This level of viability is well in excess of the mean found throughout the year in sheep-grazed swards in Wales (Dutta 1988) and New Zealand (Newton et al 1992), only 30-40% of nodes bearing branches when tested for viability. However, both recorded higher viability levels among buds on nodes produced in autumn, i.e.…”
Section: Discussionmentioning
confidence: 70%
“…Increased flowering can reduce stolon branching (Thomas 1980), as each node has the potential to produce either a flower or a branch, but the proportion of nodes supporting either a flower or a branch was low for both clovers. Newton et al (1992) noted that 40% of axillary buds may be non-viable. Loss of viability may have had a greater effect on branching than the loss of sites due to flowering in this study, as less than 6% of nodes contained flowers at any one time.…”
Section: Clover Morphologymentioning
confidence: 99%